New accounting rules for the recognition and measurement of financial instruments: Some issues implied by the IFRS 9 - Knežević Goranka; Pavlović Vladan; Stevanović Simo (Ekonomski Pogledi, 2015)
Up until now accounting standards regarding financial instruments were changed several times. The latest change was the issuance of the IFRS 9 Financial instruments published for the purpose of simplifying the rules in its predecessor IAS 39 Financial instruments: recognition and measurement. From the above mentioned changes of accounting regulatory regime for financial instruments we may conclude that accounting bodies, so far, have not found the adequate approach and treatment for the financial instruments. They considered that fair value would be a revolutionary measure for the financial instruments and that this measure would provide more relevant, transparent and comparable information. But the standard setters did not predict that this measurement attribute might have an effect on earnings power and financial position of a company. In this paper we observe critiqually the main differences between IFRS 9 and IAS 39 regarding the recognition and measurement of financial instruments and with an emphasis on of some problems of early adoption of IFRS 9 by companies.